Platelet Reactivity Was Not Associated with Infarct Size after Primary Percutaneous Coronary Intervention - Park, Seohwa; Yun, Kyeong Ho; Cho, Jae Young; Lee, Seung-Yul (Chonnam medical journal, 2021)
Potent antiplatelet therapy after primary percutaneous coronary intervention (PCI) has the potential to reduce infarct size. This study analyzed the association between on-treatment platelet reactivity and myocardial infarct size in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI. In this single-center, retrospective study, 253 patients who underwent primary PCI for STEMI were divided into two groups according to platelet reactivity measurements (53 patients in the high platelet reactivity [HPR] group and 200 in the non-HPR group). Technetium Tc-99m tetrofosmin single-photon emission computed tomography (SPECT) was performed before hospital discharge. We measured the infarct size using SPECT imaging and serial cardiac biomarker levels, and compared the infarct sizes of each group. The patients with HPR were older (65.5±13.2 vs. 60.6±12.1 years, p=0.011) than the patients with non-HPR. On the other hand, the non-HPR group had a higher incidence of smoking (26.4% vs. 51.0%, p=0.001) than the HPR group. Infarct size was similar between the two groups (22.6±17.3% vs. 24.8±17.7%, p=0.416). Multivariate analysis revealed that onset to balloon time >240 min (odds ratio [OR]=1.92; 95% confidence interval [CI]=1.08-3.40; p=0.025) and anterior infarction (OR=5.28; 95% CI=3.05-9.14; p<0.001) were independent predictors of large (>22%) infarct size. HPR was not a predictor of infarct size assessed by SPECT. The two groups also showed analogous cumulative creatinine kinase-myocardial band and troponin T levels. In conclusion, compared to non-HPR, HPR showed no significant association with myocardial infarct size measured by SPECT imaging in early phase of MI.Potent antiplatelet therapy after primary percutaneous coronary intervention (PCI) has the potential to reduce infarct size. This study analyzed the association between on-treatment platelet reactivity and myocardial infarct size in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI. In this single-center, retrospective study, 253 patients who underwent primary PCI for STEMI were divided into two groups according to platelet reactivity measurements (53 patients in the high platelet reactivity [HPR] group and 200 in the non-HPR group). Technetium Tc-99m tetrofosmin single-photon emission computed tomography (SPECT) was performed before hospital discharge. We measured the infarct size using SPECT imaging and serial cardiac biomarker levels, and compared the infarct sizes of each group. The patients with HPR were older (65.5±13.2 vs. 60.6±12.1 years, p=0.011) than the patients with non-HPR. On the other hand, the non-HPR group had a higher incidence of smoking (26.4% vs. 51.0%, p=0.001) than the HPR group. Infarct size was similar between the two groups (22.6±17.3% vs. 24.8±17.7%, p=0.416). Multivariate analysis revealed that onset to balloon time >240 min (odds ratio [OR]=1.92; 95% confidence interval [CI]=1.08-3.40; p=0.025) and anterior infarction (OR=5.28; 95% CI=3.05-9.14; p<0.001) were independent predictors of large (>22%) infarct size. HPR was not a predictor of infarct size assessed by SPECT. The two groups also showed analogous cumulative creatinine kinase-myocardial band and troponin T levels. In conclusion, compared to non-HPR, HPR showed no significant association with myocardial infarct size measured by SPECT imaging in early phase of MI.